Analysis of Dominant Factors Affecting the Mental Health of Social Media Users - Johannes Bastira Ginting; Tri Suci; Karmila Kaban; Evalatifah Nurhayti (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Sleep quality matters most for mental health among social media users—more than screen time, stress, or any demographic factor. We analyzed data from 477 social media users to identify which behavioral and psychosocial factors best predict mental well-being, as measured by a happiness index. Three factors showed significant associations: daily screen time, sleep quality, and stress levels. Respondents who spent more time on screens, slept poorly, and experienced high stress reported worse mental health. But sleep quality dominated. People with good sleep were 5.6 times more likely to report healthy mental wellbeing than those sleeping poorly (OR = 5.559; 95% CI: 2.841-10.878; p < 0.001), even after accounting for screen time and stress. Surprisingly, age, gender, physical activity, and platform choice showed no relationship with mental health. These findings challenge the assumption that simply reducing social media use improves wellbeing. Instead, public health interventions should prioritize sleep hygiene alongside, not instead of, managing screen time and stress. In our increasingly digital world, how we rest may matter more than how much we scroll